2005
DOI: 10.1007/s00705-005-0632-8
|View full text |Cite
|
Sign up to set email alerts
|

Bcl-2 inhibits the caspase-dependent apoptosis induced by SARS-CoV without affecting virus replication kinetics

Abstract: Vero cells transfected with either neo- or bcl-2-plasmid were infected with SARS-CoV at a high multiplicity of infection. Apoptosis appeared after the onset of CPE and completion of virus replication, and could be prevented by Bcl-2 expression. Apoptosis is likely mediated by the mitochondrial pathway, as demonstrated by its inhibition using Bcl-2, and by the activation of the caspase cascade, resulting in PARP cleavage. Prevention of apoptosis did not affect susceptibility to infection, kinetics and extent of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
48
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(51 citation statements)
references
References 27 publications
3
48
0
Order By: Relevance
“…We showed that over-expression of 3a induced apoptosis in Drosophila, and the results were consistent with a parallel investigation in mammalian cells [17]. It is well known that SARS-CoV infection induces apoptosis in viral-infected cells [4,11,[13][14][15] and the pro-apoptotic properties of a number of individual viral proteins have recently been revealed [12,[16][17][18][19][20][21][22]. All these Wndings illustrate that non-mammalian systems, particularly Drosophila in this study, are plausible models for the studies of viral gene functions in vivo.…”
Section: Discussionsupporting
confidence: 88%
See 4 more Smart Citations
“…We showed that over-expression of 3a induced apoptosis in Drosophila, and the results were consistent with a parallel investigation in mammalian cells [17]. It is well known that SARS-CoV infection induces apoptosis in viral-infected cells [4,11,[13][14][15] and the pro-apoptotic properties of a number of individual viral proteins have recently been revealed [12,[16][17][18][19][20][21][22]. All these Wndings illustrate that non-mammalian systems, particularly Drosophila in this study, are plausible models for the studies of viral gene functions in vivo.…”
Section: Discussionsupporting
confidence: 88%
“…It is well known that SARS-CoV infection induces apoptosis in viral-infected cells [4,11,[13][14][15] and the pro-apoptotic properties of a number of individual viral proteins have recently been revealed [12,[16][17][18][19][20][21][22]. At the mechanistic level, SARS-CoV infection has been shown to interfere with the Bcl-2 anti-apoptotic pathway [15]. Swelling of mitochondria is also found in viral-infected cells [13] which indicates a mitochondrial involvement in SARS-CoV-induced apoptosis.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations